Design of Student and Course Learning Outcomes Measurement - Kristianto, Hans; Prasetyo, Susiana; Susanti, Ratna Frida; Adithia, Mariskha Tri (Jurnal Pendidikan Indonesia, 2021)
Measurement of the outcomes becomes a vital part in OBE system to ensure the attainment of each outcome. In Indonesia, OBE was adopted in 2015 for higher education level. However, the changes were not accompanied with clear method to measure the outcomes, which became the urgency of this research. In this study, a preliminary method to measure student learning outcomes (SLO) and course learning outcomes (CLO) was presented. The measurement of SLO and CLO attainment was started by SLO mapping to courses, which usually had been done at curriculum design. Based on the mapping, formulation of CLO with a set of direct assessment was planned at the start of each course. After the teaching learning activities, a series of calculation was designed to obtain the attainment of SLO and CLO for each student, course, and whole study program. In the same time the final mark for GPA calculation of each student could also be obtained. The designed method could play an essential part in teaching-learning quality assurance and curriculum continuous improvement, which is aligned with both international and national accreditation criteria and standards. Furthermore, this study could provide insight for other study program in SLO and CLO attainment measurement.